Newmark Seismic Deformation Analysis for Geosynthetic Covers. Issue 1 (1998) - Matasovic, N.; Kavazanjian, E.; Giroud, J.P.
Abstract : This paper investigates the impact of the following five assumptions on the accuracy of Newmark seismic deformation analysis applied to geosynthetic cover systems: (i) the potential failure mass is noncompliant; (ii) the dynamic response of the potential failure mass is uncoupled from displacement (slip); (iii) permanent displacements accumulate in only one direction; (iv) vertical ground motions do not influence permanent displacement; and (v) the yield acceleration is constant. Information presented in the literature indicates the impact of the assumption of a noncompliant failure mass and the assumption of a seismic response uncoupled from displacement is insignificant for typical geosynthetic cover systems. The results of computer analyses indicate that the effects of two-way sliding and vertical ground motions can, in most practical cases, be neglected. However, the assumption of a constant yield acceleration, when based on residual (or la rge displacement) shear strength, may result in calculated displacements that are significantly larger than those calculated using a yield acceleration that degrades with accumulated displacement from a peak value to a residual, or large displacement, value. Overall, results of this investigation indicate that conventional Newmark analyses based upon residual shear strength yield conservative results when applied to geosynthetic cover systems.